Research and data-sharing policy in Sweden – neoliberal courses, forces and discourses*. (2nd October 2017) - Slavnic, Zoran
ABSTRACT: The discourse of openness has proved to be a very powerful instrument for promoting new research policies and the (neoliberal) reforms of higher education in all so-called 'advanced economies'. It has triggered positive democracy-, transparency-, and accountability-related associations when used in the context of politics, fair resource distribution when used in the sphere of public service, and free access to information and knowledge when used in the field of science and higher education. At the same time, international research shows that university autonomy is increasingly being attacked, reduced, and marginalized by the same policies. Power instances outside academia impose new criteria, such as 'accountability, ' 'performance, ' 'quality assurance, ' and 'good practice.' They also impose ideas about what good research is, which scientific method is to be prioritized, and what good data are. The process of the de-professionalization, polarization, and proletarianization of the academic profession is increasingly affecting academia. However, none of this has much in common with the open-access discourse. The purpose of this paper is to illustrate how this discussion applies to Sweden. Courses, forces, and discourses of the national research infrastructure development policy in general, and qualitative data preservation policy in particular, are described and deliberated.